From Reflection to Responsibility: A Conceptual Framework for Ethics and Value Formation in Social Studies Education - Pernantah, Piki Setri; Supriatna, Nana; Komalasari, Kokom; Nurbayani, Siti; Wiyanarti, Erlina (FKIP Universitas Lampung, 2025)
From Reflection to Responsibility: A Conceptual Framework for Ethics and Value Formation in Social Studies Education. Objective: This study aims to analyze the role of reflective thinking in strengthening students’ values and ethics, particularly within the context of Social Studies Education. The focus is directed toward identifying relevant pedagogical strategies to enhance reflective thinking skills as a foundation for character formation and responsible citizenship in the 21st century. Method: This study employed a qualitative approach through a conceptual review designed to synthesize diverse literature related to reflective thinking, ethical education, and Social Studies pedagogy. The synthesis aims to construct a new conceptual framework that explains the interrelation between reflective thinking, ethical education, and the development of students’ moral and character values. Findings: The literature synthesis suggests that reflective thinking skills can be effectively developed through problem-based, project-based, and collaborative learning methods, supported by integrating digital technology to promote ongoing reflection. The process of strengthening values and ethics requires the integration of ethical content into learning materials, the implementation of character-based learning, the utilization of digital technology in reflective learning, and educators’ moral exemplification. Within the context of Social Studies Education, Kolb’s Reflective Model provides a practical framework linking experience, reflection, conceptualization, and application, enabling students to develop reflective thinking skills to analyze values, social issues, and ethical dimensions. Conclusion: Implementing learning practices that emphasize reflective thinking has the potential to produce graduates who not only master theoretical knowledge but also possess ethical awareness, character values, and civic competence in higher education. Further empirical research is recommended to examine the effectiveness of reflective learning models and their long-term impact on students’ character formation. Keywords: reflective thinking skills, values, ethics, social studies education, character development.